2006
DOI: 10.1124/jpet.106.103697
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antidepressant-Like Effects but Not Brain-Derived Neurotrophic Factor mRNA Expression by the Novel N-Methyl-d-aspartate Receptor Antagonist Neramexane in Mice

Abstract: Improved efficacy in the treatment of depression may be achieved by the combined use of several antidepressants. In the present study, acute administration of the novel N-methyl-D-aspartate (NMDA) receptor antagonist neramexane, as well as the representative antidepressants imipramine, fluoxetine, and venlafaxine, shortened the duration of immobility in the mouse tail suspension test with a minimal effective dose of 5 mg/kg. When tested in combination, the antidepressant-like effects of 5 mg/kg imipramine, 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
1
9
0
2
Order By: Relevance
“…The decreased antidepressant effects of ketamine due to its repeated administration agrees with a recent clinical report (Liebrenz et al 2007), but contrasts with enhanced action of antidepressants ( Fig. 4; Cryan et al 2005a;Detke et al 1997) and of an NMDA receptor antagonist (Kos et al 2006a) in laboratory animals. Thus, one has to assume that ketamine displays other actions that mask its purported antidepressant-like effects after chronic treatment.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The decreased antidepressant effects of ketamine due to its repeated administration agrees with a recent clinical report (Liebrenz et al 2007), but contrasts with enhanced action of antidepressants ( Fig. 4; Cryan et al 2005a;Detke et al 1997) and of an NMDA receptor antagonist (Kos et al 2006a) in laboratory animals. Thus, one has to assume that ketamine displays other actions that mask its purported antidepressant-like effects after chronic treatment.…”
Section: Discussionsupporting
confidence: 68%
“…It has been known for more than 15 years that NMDA receptor antagonists produce antidepressant-like effects after a single administration in screening procedures like the TST and FST (Trullas and Skolnick 1990;Layer et al 1995;Kos et al 2006a). Perhaps, more compelling evidence of the antidepressant-like effect can be provided by studies employing a long-term treatment, demonstrating neurochemical changes like beta-adrenoceptor downregulation (Paul et al 1992;Layer et al 1995) and reversal of chronic mild stress-induced anhedonia (Papp and Moryl 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed with the administration of ketamine, MK-801, and DMI. Other authors have also reported antidepressant-like actions of ketamine in the TST at similar doses as those used in this study (Kos et al 2006). In the present study, CMI had antidepressant-like effect in the TST, but only at 20 mg/kg.…”
Section: Discussionmentioning
confidence: 59%
“…Preclinical findings, which evaluated the behavioral effects of rodents acutely treated with several NMDA receptor antagonists, also support this view. For example, ketamine or MK-801 acute administration decreases immobility time in the forced swimming test (FST) in rats and mice (Dhir and Kulkarni 2008;Garcia et al 2008;Poleszak et al 2007a, b) and has antidepressant effects in other animal models of depression (Chaturvedi et al 2001;Kos et al 2006;Maeng and Zarate 2007).…”
mentioning
confidence: 98%
“…In this way, chemical compounds acting on NMDA receptors could be interesting as pharmacological targets for the treatment of mood disorders. [7][8][9][10][11][12][13][14][15] Ketamine is a non-competitive antagonist to the phencyclidine site of NMDA glutamate receptor, which works in a use-and voltage-dependent manner. 16 Clinical studies suggested that acute administration of ketamine ameliorate depressive symptoms in patients suffering from major depression.…”
Section: Introductionmentioning
confidence: 99%